The Strategic Role of the Constitutional Court of the Republic of Indonesia Has the Potential to Amend the 1945 Constitution of the Republic of Indonesia (Implications of the Constitutional Court Decision Number 116/PUU-XXI/2023) - Sagalane, Andra Bani; Mandala, Subianta (Asian Journal of Social and Humanities, 2025)
State legal policy reflects the state's interest in securing national objectives through norms that are enacted, implemented, and enforced for the welfare of citizens, state institutions, and all related entities. Article 1, paragraph (3) of the 1945 Constitution of the Republic of Indonesia defines Indonesia as a "state of law," which includes both written and unwritten norms. Among these, laws are created by legislative and executive institutions to regulate state affairs. The hierarchy of regulations places the MPR Decree below the Law, with the Constitution as the highest authority. This study explores the gap in the construction of laws and regulations, focusing on the concept of "Faction," which appears in various laws but not in the Constitution. Through qualitative descriptive analysis and a normative legal approach, this research examines the implications of the 4% national vote threshold for political parties in the General Election, as it relates to the term "Faction" in the Indonesian House of Representatives (DPR). This study advocates for the removal of the "Faction" provisions, suggesting that even a single-member political party should not be hindered by the threshold. It proposes that the Constitutional Court could amend laws containing the term "Faction" or incorporate it into the Constitution to ensure greater inclusivity in the legislative process. The findings suggest a need for constitutional amendment to align legislative practices with democratic principles.